Metformin prevents the increase of nitric oxide and lipid peroxidation induced by dehydroepiandrosterone in early pregnant mice - Luchetti, Carolina Griselda (2013)
The aim of this work was to study the effects of dehydroepiandrosterone (DHEA) and metformin (M) on nitric oxide (NO) system and oxidative stress in embryo implantation sites of early pregnant mice. The biguanide M is used for treating polycystic ovary syndrome but its complete mechanism of action remains unknown. Nitric oxide (NO) has important protective roles during pregnancy, keeping uterine relaxation and vascular function. However, its overproduction leads to nitrative stress by producing reactive nitrogen species. Here we measured NO content by Griess method and the localization of inducible and endothelial nitric oxide synthase (iNOS and eNOS) by immunohistochemistry in implantation sites. Also we measured lipid peroxidation by TBA-RS, glutathion by Ellman’s reaction and antioxidant enzymes by enzymatic kinetics in uterine homogenates. We found that the expression of both iNOS and eNOS and the NO content were increased with DHEA (p<0.001 for all) and restored to control levels with DHEA+M. Oxidative stress: DHEA increased lipid peroxidation (p<0.01) and glutathione (GSH, p<0.01). With DHEA+M lipid peroxidation was restored to control levels. The activities of the antioxidant enzymes superoxide dismutase and catalase were not modified. We conclude that hyperandrogenization with DHEA enhances the NO system and lipid peroxidation in implantation sites of early pregnant mice and that M treatment prevents these effects.